Chronic inflammatory demyelinating polyradiculoneuropathy complicating anti TNF α therapy for chronic plaque psoriasis. (1st December 2011) - Ahmed, Zahra; Powell, Robert; Llewelyn, Gareth; Anstey, Alex
Abstract : A 53-year-old woman with chronic plaque psoriasis treated with adalimumab (antitumour necrosis factor (anti TNF) α therapy) for 10 months presented with an 8 week history of hyperesthesia in a 'glove and stocking' distribution and clumsiness on walking. Nerve conduction studies confirmed the clinical diagnosis of a chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). She was admitted and treated with intravenous immunoglobulin and oral steroids and made an excellent recovery. To our knowledge, this is the first published report of CIDP associated with anti TNF α therapy given to treat psoriasis.